Answer :

Answer:

Step-by-step explanation:

Considering the given triangle QED, to determine ED, we would apply the sine rule. It is expressed as

a/SinA = b/SinB = c/SinC

Where a, b and c are the length of each side of the triangle and angle A, Angle B and angle C are the corresponding angles of the triangle. Likening it to the given triangle, the expression becomes

ED/SinQ = EQ/SinD = QD/SinE

Therefore

ED/Sin 49 = 2/Sin 35

Cross multiplying, it becomes

EDSin35 = 2Sin49

0.574ED = 2 × 0.755

0.574ED = 1.51

ED = 1.51/0.574

ED = 2.63 in